(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The rapid integration of artificial intelligence into clinical practice has generated one of the most pressing questions in contemporary civil law: whether patients possess an enforceable right to receive a meaningful explanation of AI-generated medical decisions, and what legal mechanisms exist to protect this interest. The article examines the normative foundations of the right to explanation in international and comparative law, analyses the civil liability consequences of its violation, and evaluates the adequacy of existing legal instruments. The author concludes that the right to explanation in AI medical systems constitutes an emerging but insufficiently codified civil right, the protection of which requires a coherent framework combining data protection, product liability and health law